Speaking Content Analysis in Indonesian Vocational High School English Textbook - Uswatun Khasanah; Ro'ifah Ro'ifah; Sulton Dedi Wijaya (Universitas Jambi, Magister Program of English Education Department, 2022)
This study aimed to determine the appropriateness of speaking content in Class XII vocational high school English textbooks in light of the new Indonesian curriculum, the Kurikulum Merdeka. The transition from the Kurikulum 2013 to the Kurikulum Merdeka requires teachers to modify teaching materials, making it important to understand if existing English textbooks can be adapted. The research methodology was qualitative and descriptive, utilizing document analysis of the students' English textbook,